Análise microbiológica e parasitológica de alimentos servidos em escolas do ensino infantil e fundamental de uma cidade da região de São José do Rio Preto - SP - Anselmo, Daiane Bertholin [UNESP] (2014)
The health safety is highly compromised when meals are prepared in large quantities, usually seen in educational institutions that serve meals daily, endangering the health of children. Several diseases and malaise of the population are due to the intake of contaminated dishes and water, due to the presence of pathogenic micro-organisms or producers toxins, being necessary to assess the quality of food and knowledge of food handlers on food security. Therefore, the aim of this project is to assess the sanitary-hygienic aspects of food produced in a kitchen pilot, of the meals distributed in all educational institutions of a city region São José do Rio Preto – SP, and the menu served to the children will also be examined through microbiological and parasitological analysis. This research evaluated 102 samples of different types of food, 73 swab samples from the hands and surfaces, 60 water samples from the drinking fountains and faucets at the pilot kitchen, and the water following was subjected from microbiological analysis: heterotrophic bacteria, total coliforms, thermotolerant coliforms and Escherichia coli along with yeast and molds. In foods were analyzed: total coliforms, thermotolerant, search E. coli and Salmonella spp. count, coagulase positive Staphylococci, Bacillus cereus and sulfite-reducing Clostridia. From the swabs were evaluated: total coliforms, thermotolerant, search E. coli, and coagulase positive Staphylococci, while aerobic mesophilic bacteria were exclusively analyzed in the surfaces. Coliform bacteria were found in the water of a crate inside the pilot kitchen and E. coli in the drinking fountains the school A. Counts were found >1.100 MPN of total coliforms, <3 a 240 MPN of thermotolerant coliforms and E. coli; 2x102 CFU/g of Bacillus cereus; <10 a 4x105 CFU/cm2 of aerobic mesophilic bacteria; <100 a 1,8x105 CFU of Staphylococcus spp., being that 6x103 CFU/g, 1,6x104 CFU/hands swab and 5x101 CFU/cm2 were ...